Assessing maternal and perinatal complication incidence in pregnant patients with sickle cell disease: a retrospective analysis of transfusion therapy at a tertiary care hospital - Thirugnanasambandam, Ram Prakash; Muthu, John (Frontiers in Hematology, 2025)
BackgroundPregnant individuals with sickle cell disease (SCD) face high maternal and fetal complication rates. While some studies suggest transfusions may improve outcomes, evidence is limited. This study analyzed maternal and fetal complications in pregnant SCD patients of different genotypes who received transfusions.MethodsWe performed a retrospective review of medical records at New York City Health and Hospitals/Kings County over nine years (2015–2024), including all pregnant patients with SCD (N=42). Maternal and fetal complications were analyzed based on genotype, hemoglobin levels, age, and raceResultsPatients with homozygous sickle cell disease (HbSS) comprised 69% of the cohort, with most HbSS patients over 35 years old. Baseline hemoglobin levels were 7.2 g/dl for HbSS, 9.5 g/dl for HbSC, and 7.0 g/dl for HbS Beta+ thalassemia. Transfusion needs were highest in HbSS patients (72.4%) compared to HbSC (44.4%) and HbS Beta+ thalassemia (25%) but were not statistically significant. Obstetric complications such as pre-eclampsia (20.7%) and postpartum hemorrhage (17.2%) were more common in HbSS patients but without statistical significance. Fetal complications included intrauterine growth restriction (6.9%) in HbSS patients and fetal distress (22.2%) in HbSC patients with no significant differences. Comparing transfused and non-transfused HbSS patients, transfused patients had lower hemoglobin levels and more vaso-occlusive episodes. However, obstetric and fetal complications were similar in both groups.ConclusionDespite transfusions, HbSS patients experienced more complications. A personalized, evidence-based approach is needed for managing SCD pregnancies, focusing on transfusion timing, comorbidities, and fetal monitoring.